"Make Sure Somebody Will Survive from This": Transformative Practices of Hope among Danish Organ Donor Families. (15th February 2016) - Jensen, Anja M. B.
Abstract : Based on anthropological fieldwork among Danish organ donor families and hospital staff in neurointensive care units, this article explores the transformative practices of hope in Danish organ donation. Focusing on various phases of the organ donation process, I demonstrate how families and professionals practice hope in astounding ways: when hoping for organs, when hoping for the end of patient suffering, when hoping for the usability of the donor body, and when hoping to help future donor families by sharing painful experiences. By focusing on such practices and transformations of hope, this article sheds light on the social negotiations of life and death among families and staffs in medical contexts and describes how the dignity of the deceased donor and the usability of the donor body are closely connected in family attempts to make donation decisions meaningful during and after a tragic death.